Board independence, CEO tenure, and private firm performance in Nairobi, Kenya - Protus, Chepkwony; Tuwey, Joel (International Journal of Emerging Trends in Social Sciences, 2024)
Governing board members includes a mix of non-executive and executive members who seek the best interests of shareholders. Non-executive board members relay on independence to execute their responsibilities and enables better firms’ performance. The independent board members are vetted in by shareholders to reduce agency problems. The study aims to establish how Chief executive officer tenure influence independent board members on decision making to enhance firm performance. Agency theory and stewardship theory were utilized in the study. The explanatory research design was used 371 private firms were the sample size. Data was collected using structured questionnaires. Hierarchical multiple regression models were used to test for direct effect and moderation effect. According to the findings, board member independence is critical for monitoring the CEO and reducing principal-agent conflict, hence enhancing business performance. The independence of board members is critical for organizations to remain inventive and competitive in order to improve firm performance.